The Role of Artificial Intelligence-Based Technology with ChatGPT as an Educational Learning Media Innovation in Indonesia - Nita, Sekreningsih; Sussolaikah, Kelik; Aldida, Jovansa Denis (International Journal of Multidisciplinary Sciences and Arts, 2023)
ChatGPT with OpenAI is an artificial intelligence-based machine technology that is trained to imitate human conversation using NLP (Natural Language Processing) technology. ChatGPT can be used to produce quite scientific writing with good and effective formulation techniques. With the help of OpenAI technology, ChatGpt can help innovate in creating learning media and learning tools such as creating RPS (Semester Learning Plans) and writing textbooks for teaching staff, especially at the tertiary level. The aim of this research is to clarify the role of artificial intelligence in the world of education and this research method uses qualitative methods. The results of experiments carried out by researchers using ChatGPT produced + 693 words of writing, this number can still be developed further. The time speed only requires + 5-7 minutes to complete this experiment and includes time to document the processing results from ChatGPT.In conclusion, ChatGPT is useful, namely teaching, research and community service. So the presence of ChatGPT as a tool in creating scientific works, learning tools (RPS) and textbooks. Another benefit of ChatGpt, especially in developing the competencies (skills) of teaching staff (lecturers), can help carry out the Tri Dharma of Higher Education technology opens up opportunities to utilize this AI chatbot for education in Indonesia